PEMERINTAHAN PUSAT DAN SWAPRAJA: MASALAH SENTRALISASI DAN DESENTRALISASI - Ardhana, I Ketut (Jurnal Masyarakat dan Budaya, 2005)
This paper discusses the historical process in the context of the government system in Nusa Tenggara. This paper particularly analyses the bargaining position of the people of Nusa Tenggara in gaining the status of their region as a province. Indeed, the name of Nusa Tenggara as a region in the Indonesian archipelago had not been known before the formation of the Republic of Indonesia. Based upon the historical evidences, the external factors had considerably affected the patterns of the traditional political and social systems. Prior to the colonial era, there were several chiefdoms which were fragmented and competed to one another. The coming of the colonial Dutch has transformed the traditional political systems to a more modern system in which the colonial Dutch introduced a new system, the province of Timor, Residentie Timor en onderhoorigheden. This province has been changed to be the province of Nusa Tenggara since the Indonesian independence.